Effects of metformin alone or in combination with vitamin C and E on serum glucose concentration and lipid profile in type 2 diabetic patients - Abdul Munim Al-Thanoon, Zeina; Hamo Mahmood, Isam; Abdul Jabbar, Imad (Tikrit Journal of Pharmaceutical Sciences, 2023)
The present study was aimed to evaluate the effects of metformin alone or in combination with vitamin C and E on fasting serum glucose (FSG) concentration and lipid profile in type 2 diabetic patients. One hundred and three newly diagnosed type 2 diabetic patients participated in this study. They were divided into 3 groups according to treatment. The first group involved 32 patients were kept on metformin therapy alone. The second group involved 37 patients were kept on combination of metformin and vitamin C and vitamin E . Whereas the third group involved 34 patients were have no drug therapy but kept on diet restriction. The duration of treatment was for 2 months . Another group consisted of 35 healthy subjects participated in the study as a control group. Body mass index (BMI) was calculated by Quetelet index (Weight/Height2). Fasting serum blood samples were used for measuring serum glucose concentrations and lipid profile using special commercial kits. Serum LDL-c concentration was calculated by Friedewald equation and atherogenic Index was calculated as TC /HDL-c . The results found that there were a significant elevation in weight, BMI, FSG, Tc ,TGS, LDL-c and AI and a significant reduction in HDL-c in type 2 diabetic patient before starting treatment as compared with control group. The results also found that metformin group showed a reduction only in weight, BMI, FSG and Tc whereas the combination group showed a highly significant reduction of all studied parameters and significant elevation of HDL-c. The diet group showed non significant changes in all of the studied parameters. This study has been concluded that the addition of Vitamin C and E to metformin therapy produce additional beneficial effects on weight, BMI ,FSG and lipid profile over metformin alone or diet therapy alone in type 2 diabetic patients.